Generation Y medical doctors’ experiences of a positive psychology 2.0 intervention for burnout in a South African public hospital - Oosthuizen, Rudolf M.; Disemelo, Keitumetse; Mayer, Claude-Hélène (Frontiers in Psychology, 2022)
The aim of the research was to explore experiences of a Positive Psychology 2.0 (PP2.0) intervention for burnout among Generation Y medical doctors working in a South African public hospital. The emphasis was on the potential benefits and recommended intervention amendments in a specific cultural context of South Africa. A phenomenological approach was followed in the collective case study. The Maslach Burnout Inventory was administered in phases I and III to quantify the level of burnout. This study offers findings that could be incorporated into a bigger burnout intervention strategy in the South African public hospital, involving all stakeholders to ensure that burnout is combatted on a long-term basis. Furthermore, the findings emphasized certain culture-specific structural issues and the impact that the neglection of burnout has on newly qualified medical doctors working in a South African public hospital and patients in their care. Certain recommendations were made for the South African public hospital for future research in PP2.0 interventions and for facilitators working with burnout among newly qualified medical doctors.